Patient acceptance of osteoporosis treatment: Application of the stages of change model. (June 2016) - Sujic, R.; Beaton, D.E.; Bogoch, E.R.
Highlights: Most patients occupy the first or the last two stages of change. Two-stage model is valuable in describing patient aptitude to initiate treatment. Baseline factors predicting who is less likely to initiate treatment are identified. Abstract: Objectives: To examine whether a commonly used model of behaviour change, stages of change, is helpful in understanding osteoporosis treatment initiation in a cohort of fragility fracture patients. Study design: This longitudinal cohort study used data from a provincial osteoporosis screening program targeting fragility fracture patients age 50 and over. Logistic regression was used to identify baseline factors associated with patients moving from the first, pre-contemplation stage at baseline to the more advanced stages of action/maintenance at follow-up, when treatment is initiated and maintained. Main outcome measure: Patient's stage-of-change readiness to accept osteoporosis treatment. Results: At baseline, 91% of patients were in the pre-contemplation stage. Of these, 74.1% remained at the same stage at follow-up, 2.7% moved to contemplation and preparation while 23.2% moved to action/maintenance. The adjusted analysis showed that those who moved from pre-contemplation to action/maintenance were more likely to have a previous fracture OR 1.5 (1.1–2.0), history of oral steroid use OR 2.1 (1.3–3.5), higher perceived benefits to osteoporosis drug treatment OR 1.2 (1.0–1.3), perception of bones as "thin" OR 2.8 (2.0–4.0) and were less likely to perceive that they were taking too many medications OR 0.6 (0.5–0.9). Conclusions: With the majority of patients in the pre-contemplation and the action/maintenance stages, our results suggest an existence of a two-stage model. The baseline factors that we identified can be used to predict which patients are less likely to initiate treatment, which in turn, can be used to inform post-fracture interventions and facilitate behaviour change.